A resorbable shape‐memory starch‐based stent for the treatment of salivary ducts under sialendoscopic surgery. (17th December 2013) - Beilvert, Anne; Faure, Frédéric; Meddahi‐Pellé, Anne; Chaunier, Laurent; Guilois, Sophie; Chaubet, Frédéric; Lourdin, Denis; Bizeau, Alain
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis In sialendoscopy, stents are often used to keep the salivary duct open after surgery. These stents need to be removed. Recently, our group developed a new starch‐based shape‐memory material that is a widespread degradable polymer. Such a device could be manufactured into a deployable resorbable stent to keep the salivary duct open before in situ degradation. An experimental test was performed to establish a methodology and to evaluate the feasibility of the starch stent implantation in an animal model with clinical equipment. Study Design Evaluation of different formulations—potato and high amylose content maize starch without and with plasticizer—with laboratory bench‐top testing and in vivo evaluation in a large‐animal model. Methods Starch‐based stents were manufactured. They were evaluated for their shape‐memory properties (water, 37°C) and their degradability in simulated saliva in both static and flow conditions mimicking salivary flow in the submandibular duct. A pilot study of stent implantation was then performed in vivo in a large‐animal model to assess that the stent dimensions were consistent for implantation in the submandibular duct. Results Stents made from plasticized starch had the required shape‐memory properties to be used as self‐deploying stents. However, starch‐based stents were rapidly hydrolyzed in simulated saliva. Stents could be directly inserted in the dilated salivary duct in a pig model without harming the epithelium. Conclusions Shape‐memory stents with suitable geometry for sialendoscopic surgical procedure can be fabricated and inserted in the submandibular duct. Starch‐based stents can be used in other pathologies with less α‐amylase content in the surrounding medium. Level of Evidence NA. Laryngoscope, 124:875–881, 2014